Cosmos caudatus Kunth. extract reduced number of microflora in oyster mushroom (Pleurotus ostreatus) - Yusoff, N. A. H.; Sanuan, F. M.; Rukayadi, Yaya (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
Nowadays consumer is more demand on natural foodstuff instead of synthetic product due to their concern on health. The objective of this study is to investigate the effect of C. caudatus extract on the number of microflora in oyster mushroom at different concentration of C. caudatus extract and exposure time using dilution method. The results showed that the number of microorganisms (Log10 CFU/g) in oyster mushroom in term of Total Plate Count (TPC), Bacillus cereus, Escherichia coli and Staphylococcus aureus were 6.13 ± 0.04, 6.15 ± 0.09, 5.97 ± 0.04, and 6.46 ± 0.00, respectively. The effect of C. caudatus extract on microflora in oyster mushroom at concentrations of 0.00%, 0.05%, 0.5%, and 5.0% with exposure time of 0, 5, 10, and 15 min demonstrated that the reduction number of microflora in oyster mushroom was dependent on the concentration of C. caudatus extract and exposure times. The number of TPC (Log10 CFU/g) in oyster mushroom was significantly reduced after treated with C. caudatus extract at concentration of 0.05% for 15 min; 6.13 ± 0.04 reduced to 2.62 ± 0.07. Moreover, B. cereus (Log10 CFU/g) in oyster mushroom was significantly reduced by treatment of C. caudatus extract at concentration of 0.05% for 5 min; 6.15 ± 0.09 reduced to 3.77 ± 0.15. Meanwhile, the number of E. coli (Log10 CFU/g) in oyster mushroom was significantly reduced at concentration of 0.05% for 10 min; 5.97 ± 0.04 reduced to 3.21 ± 0.13. Lastly, the survival number of S. aureus in oyster mushroom was significantly reduced after treated with C. caudatus extract at concentration of 0.05% for 15 min; 6.46 ± 0.00 reduced to 4.83 ± 0.07. In conclusion, C. caudatus extract has potentiality to be developed as natural sanitizer for rinsing raw food materials such as oyster mushroom.